Contemporary urologic minilaparoscopy : indications, techniques, and surgical outcomes in a multi-institutional European cohort - Lima, Estêvão Augusto Rodrigues de (2013)
OBJECTIVES: To provide an analytical overview of contemporary indications, techniques, and outcomes of urologic minilaparoscopy (ML) in multiple European centers. METHODS: Data of patients who had undergone a minilaparoscopic urologic procedure at nine European institutions between 2009 and 2012 were retrospectively gathered. Surgical procedures were classified as upper or lower urinary tract and as ablative or extirpative and reconstructive. The main surgical outcome parameters were analyzed and relevant operative data related to the surgical technique were recorded. RESULTS: Overall, 192 patients (mean age 45.25±17.8 years) were included in the analysis. Most of them were nonobese (mean body mass index [BMI] 24.7±3.6?kg/m(2)) at low estimated surgical risk (mean American Society of Anesthesiologists [ASA] 1.69±0.68). Indications for surgery were mostly nononcologic (132 cases, 68.8%). Most of the procedures were done in the upper urinary tract (133 cases, 69.2%) and were mostly with a reconstructive intent (109 cases, 56.7%). Overall operative time was 132.7±52.3 minutes with an estimated blood loss of 60.9±47.6?mL while the mean hospital stay was 5±2.1 days. Most of the postoperative complications were low Clavien grade (1 and 2), with only one (0.5%) grade 3 and one (0.5%) grade 4 complications recorded. CONCLUSIONS: A broad range of common procedures can be safely and effectively performed with ML techniques. By duplicating the principles of standard laparoscopy, but potentially offering less surgical scar and trauma, ML can be regarded as a viable option when looking for a virtually "scarless" surgery.